1995
DOI: 10.1111/j.1365-2672.1995.tb03152.x
|View full text |Cite
|
Sign up to set email alerts
|

Ribotyping and plasmid profiling of Vibrio anguillarum serovar O2 and Vibrio ordalii

Abstract: One hundred and twenty-nine strains of Vibrio anguillarum serovar O2 and 14 strains of Vibrio ordalii were ribotyped and examined for plasmid contents. A total of 35 different ribotypes were detected. The V. anguillarum serovar O2 strains were divided into 32 different ribotypes. The V. ordalii strains showed three different ribotypes, clearly distinct from those of the V. anguillarum strains. Ribotypes were separated into seven clusters, of which one comprised the V. ordalii strains. Clustering of the strains… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
24
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(30 citation statements)
references
References 28 publications
6
24
0
Order By: Relevance
“…This figure is somewhat lower than previously reported by Larsen and Olsen [13] who found that 54 out of 103 (52%) 02 strains carried plasmids. Tiainen and colleagues [33] detected plasmids in 48 out of 129 (37 %) 02 strains, a figure comparable to that reported in the present study. However, Tiainen and colleagues [33] found a remarkable difference between northern European and southern European strains.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This figure is somewhat lower than previously reported by Larsen and Olsen [13] who found that 54 out of 103 (52%) 02 strains carried plasmids. Tiainen and colleagues [33] detected plasmids in 48 out of 129 (37 %) 02 strains, a figure comparable to that reported in the present study. However, Tiainen and colleagues [33] found a remarkable difference between northern European and southern European strains.…”
Section: Discussionsupporting
confidence: 92%
“…Tiainen and colleagues [33] detected plasmids in 48 out of 129 (37 %) 02 strains, a figure comparable to that reported in the present study. However, Tiainen and colleagues [33] found a remarkable difference between northern European and southern European strains. Plasmids were almost exclusively found in the northern European isolates, and since in the study by Larsen and Olsen [13] only Danish isolates were included, this may very well account for the reported difference in ,,t tr _ ) Rt C' £, _" _q (7 plasmid content.…”
Section: Discussionsupporting
confidence: 92%
“…A plasmid of approximately 32 kb has been detected in all V. ordalii strains studied so far [3,5,8]. The plasmid of the V. ordalii type strain, DF3K, has been designated pMJ101 [1].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, the clinical symptoms and pathological changes caused by this organism in fish are different from those recorded for V. anguillarum [7]. It was recently demonstrated that V. ordalii and V. anguillarum were easily distinguished by ribotyping [8]. V. ordalii cross-reacts serologically with V. anguillarum serogroup 02a [9] although minor antigenic differences have been demonstrated.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation